Upaya Penerapan Kecerdasan Emosional Dalam Meningkatkan Prestasi Akademik - Bwarleling, Theresia Hesti; Nelson, Catheryn Iona (Universitas Bunda Mulia, 2023)
Accounting is a precise field of science, meaning it only provides a small tolerance for error. Therefore, a thorough and detailed learning pattern is needed for Accounting teaching staff. To achieve this, it is necessary to grow the role of emotional intelligence of accounting educators in order to further motivate students to continue studying complex accounting knowledge. In addition, students are also expected to continue to adapt and be willing to learn to develop themselves, have strong competitiveness, as well as be able to think logically and critically. Lastly, they are also expected to keep abreast of technological developments and the digital world in order to be able to apply them in the field of accounting (Accounting as a STEM – Science Technology Engineering Mathematics Subject). From the calculation of the correlation coefficient between the survey results for the level of emotional intelligence of educators and the results of observations of all students through the average value of the assignments obtained; it is revealed that there is a relationship rate of 54.9%. Through the acquisition of these results, it can be concluded that there is a relationship between the emotional abilities of UBM teaching staff in reading situations during the teaching and learning process with the needs of the students so that the results (output in the form of values) obtained can be more optimal.